Extramedullary Hematopoiesis in the Sinonasal Cavity: A Case Report and Review of the Literature - Carly A. Clark BA; Cameron P. Worden BS; Brian D. Thorp MD; Charles S. Ebert MD/MPH; Adam M. Zanation MD; Brent A. Senior MD; Steven M. Johnson MD; Wade G. McClain DO; Adam J. Kimple MD, PhD (Allergy & Rhinology, 2020)
Background Extramedullary hematopoiesis (EMH) occurs in patients with hematologic disorders, but rarely within the paranasal sinuses. We report a case of EMH in a 17-year-old male with sickle cell disease (SCD) who presented with occipital pain and sinusitis. A computed tomography (CT) scan demonstrated heterogeneous opacification of the right maxillary sinus concerning for allergic fungal sinusitis or a fungal ball with bony erosion. He was taken to the operating room for endoscopic biopsy and a limited endoscopic sinus surgery. Grossly, his maxillary sinus was filled with spiculated osseous tissue. Final pathology demonstrated active hematopoietic bone marrow filling the sinus. Methods We present a case report and literature review of sinonasal EMH. Results We identified 14 articles with 15 patients. EMH was typically associated with SCD or beta thalassemia. The average age of presentation was 30. There was a male sex predilection with a ratio of 11:15. The most common presenting symptom was a headache and nasal obstruction (33% for both). The most common finding on CT was a soft tissue expansile mass (73%). The most commonly affected location was the maxillary sinus (60%). Conclusions This case report serves as a reminder to consider EMH as an uncommon cause of sinus opacification, particularly in patients with SCD or beta thalassemia. The expansion of hematopoietic tissue may be identified as a sinus mass on CT. By recognizing the potential manifestations of chronic anemia, an accurate and timely diagnosis can be made.